2014
DOI: 10.1039/c4cc02981j
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent silver nanoclusters stabilized by DNA scaffolds

Abstract: Fluorescent silver nanoclusters, in particular DNA stabilized (templated) silver nanoclusters, have attracted much attention because of their molecule-like optical properties, strong fluorescence and good biocompatibility. In this feature article, we summarize the DNA stabilized silver nanoclusters from the viewpoints of synthesis, optical properties, as well as recent applications in biological detection and imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
123
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(123 citation statements)
references
References 195 publications
(195 reference statements)
0
123
0
Order By: Relevance
“…58 Their results are similar to our results on silver clusters. They concluded that their lowest energy structures were the triangle for Au 3 , trapezoid (called diamond in this work) for Au 4 , X (bowtie) for Au 5 , W (trapezoid) for Au 5 + , and triangle for Au 6 . 58…”
Section: -3mentioning
confidence: 99%
See 3 more Smart Citations
“…58 Their results are similar to our results on silver clusters. They concluded that their lowest energy structures were the triangle for Au 3 , trapezoid (called diamond in this work) for Au 4 , X (bowtie) for Au 5 , W (trapezoid) for Au 5 + , and triangle for Au 6 . 58…”
Section: -3mentioning
confidence: 99%
“…Many studies have been performed to understand the effects from the DNA base pairs on the small AgNCs (∼Ag 2 -Ag 30 ) 18,[29][30][31][32] and some provide insights into creating AgNCs using different DNA platforms. 4,5,8,10 Their findings indicate that it is possible to manipulate the size and formation of these nanomaterials by employing strands of DNA with specific sequences. 3,18,29,30,32 Dickson, Petty, and coworkers have shown that very small (n < 10) AgNCs can be synthesized by exploiting the DNA sequence.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Attachment of ultra-bright BODIPY dyes and semiconductor nanocrystals called quantum dots (QDs) is especially promising for applications in fluorescent microscopy ( Figure 3D) [28,29]. In addition, fluorescent metal nanoclusters (for example, silver-or gold-based) have attractive optical qualities, which may increase the sensitivity of nucleic acid detection [30,31]. Remarkably, metal nanoclusters can detect natural nucleic acids, such as cancer related mRNAs, directly in living cells [31].…”
Section: Enzyme-free Hybridization Assays: Specificity In Focusmentioning
confidence: 99%